2013
DOI: 10.1155/2013/216518
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Halogen Bonding between Pyridine and Perfluoroalkyl Iodide in Solution Phase Using the Combination of FTIR and19F NMR

Abstract: Halogen bonding between pyridine and heptafluoro-2-iodopropane (iso-C3F7I)/heptafluoro-1-iodopropane (1-C3F7I) was studied using a combination of FTIR and 19F NMR. The ring breathing vibration of pyridine underwent a blue shift upon the formation of halogen bonds with both iso-C3F7I and 1-C3F7I. The magnitudes of the shifts and the equilibrium constants for the halogen-bonded complex formation were found to depend not only on the structure of the halocarbon, but also on the solvent. The halogen bond also affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…Typical complexes for which a detailed microwave study is now reported include the complex of ammonia with CF 3 Cl [50] and the 1:1 adducts of CF 3 I with ammonia and trimethylamine [53]. Related complexes recently investigated using IR and NMR spectroscopy [56] are formed between pyridine and the perfluoroalkyl iodides heptafluoro-2-iodopropane (iso-C 3 F 7 I) and heptafluoro-1-iodopropane (1-C 3 F 7 I). …”
Section: C-x N-bonded Complexes: Trimethylaminementioning
confidence: 99%
See 1 more Smart Citation
“…Typical complexes for which a detailed microwave study is now reported include the complex of ammonia with CF 3 Cl [50] and the 1:1 adducts of CF 3 I with ammonia and trimethylamine [53]. Related complexes recently investigated using IR and NMR spectroscopy [56] are formed between pyridine and the perfluoroalkyl iodides heptafluoro-2-iodopropane (iso-C 3 F 7 I) and heptafluoro-1-iodopropane (1-C 3 F 7 I). …”
Section: C-x N-bonded Complexes: Trimethylaminementioning
confidence: 99%
“…Before discussing the methodology used and the results obtained during the cryospectroscopic experiments, it is worth noting that, since the first experiments reported in 2009 [48], a variety of complexes strongly related to those studied in the cryosolutions have now also been investigated using traditional and chirped-pulsed microwave studies [49][50][51][52][53][54][55], and that additional information on complexes between more complex perfluoro alkyl iodides and pyridine has also been obtained using low-temperature IR and NMR experiments [56].…”
Section: Introductionmentioning
confidence: 99%
“…Twelve co-crystallizations were performed using three acceptor molecules with two different acceptor sites on each of them and four perfluoroiodoalkanes. IR spectroscopy was again found to be a versatile, convenient and accurate screening method for determining if a particular combination of donors and acceptor resulted in the formation of a co-crystal [38][39][40]. With the formation of new intermolecular interactions between donor and acceptor, some of the original stretching bonds are affected although it is sometimes difficult to find obvious patterns to the way in which some of modes are red or blue shifts compared to their original positions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, fluorinated functional groups are incorporated into molecules for novel functions in materials science and in the biomedical field (Kirsch, 2004). A significant number of fluorinated pyridinium salts have been studied with regard to structure and bonding (Hawthorne et al, 2013;Hensen et al, 1988;Mootz & Hocken, 1989), including those with multi-substituted fluorinated side chains (Rocaboy et al, 2002). Pyridine and its derivatives are especially important in modern clinical use, taking advantage of their many biological activities (Altaf et al, 2015).…”
Section: Introductionmentioning
confidence: 99%